Los mamíferos fósiles del Pleistoceno tardío-holoceno temprano del sudeste de la provincia de Córdoba y sus implicancias paleoambientales para el centro de Argentina - Luna, Carlos Alberto (2014)
Paleontological exploration on the eastern plain of Córdoba Province is scarce, only referring to mammal assemblages from Mar Chiquita lake or San Francisco localities in the northeast of the Córdoba province, or specifi c discoveries in the centre and southeast of this province. In the present study is described a new faunistic assemblage from Isla Verde, in the southeast plain of Cordoba province. This assemblage is composed by Eutatus seguini Gervais, Zaedyus pichiy (Desmarest) Osgood, Tolypeutes sp., Neosclerocalyptus sp., N. paskoensis (Zurita) (Cingulata), Scelidotheriinae indet. (Tardigrada), Ctenomys sp., Lagostomus sp., Galea sp. (Rodentia), Macrauchenia sp. (Litopterna) and Equus (Amerhippus) sp. (Perissodactyla). This fauna is refered to Lujanian Stage (late Pleistocene-early Holocene) of the Pampean Region. The fossiliferous level is consistent with a semiarid and herbaceous steppe and refers to La Invernada Formation. From a paleoclimatic point of view, the record of these species suggests arid to semiarid conditions, between cold and warm. These conditions also agree with the interpretations realized studying morphological adaptations of some fossils.